Students’ Approaches to Teaching and Learning in Institutions of Higher Education - Zuzevičiūtė, Vaiva (Acta Paedagogica Vilnensia, 2004)
The aim of the paper is to analyse both approaches to learning and factors influencing deep approach to learning. Methods of literature analyses and questionnaires were employed in order to identify approaches to learning in Lithuanian higher education. Concepts of learning, developed by Marton and Saljo, together with approaches (surface and deep) were employed in order to identify situation. Ideas of Lithuanian and foreign scientists (L. Jovaiša, L. Šiaučiukėnienė, R. Laužackas, L. Kraujutaitytė, P. Jucevičienė, R. Bamett, P. Ramsden) were employed in order to identify the most important elements of learning. Motivations, fostering of independence, learning analysis, assessment, have been identified as important factors for deep approach to learning. Results of the study revealed that a relation between approaches to learning and age, and study stage exists in some instances. A majority of students agree that their teachers motivate them to learn to their full capacity (46.1 percent). Concerning independence; it seems to be promoted in institutions of higher education: majority (75.5 percent) of students reported to be encouraged to develop their academic interests independently, and 45.5 percent of students reported having opportunity to choose themes for more in-depth studies. A majority of students do not feel having an impact on the way they are going to be assessed, more than a third do not have opinions about the issue. It seems, assessment is far beyond the practice of students; therefore they are unable to evaluate the situation. A conclusion about the need to promote deep approach to learning in order to promote the competence of lifelong learning in institutions of higher education is presented.
Keywords: active learning; paradigm of learning; deep approach to learning